Epidemiology of Imported Malaria Cases in Japan, 2006–2014: A Sentinel Traveler Surveillance Approach - Kanayama, Atsuhiro; Arima, Yuzo; Matsui, Tamano; Kaku, Koki; Kinoshita, Hitomi; Oishi, Kazunori (The American journal of tropical medicine and hygiene, 2017)
Malaria continues to be imported into Japan. To better assess the risk of imported malaria, we describe malaria species, suspected country/area of infection (accounting for the number of travelers), demographic characteristics, clinical manifestation, and healthcare access, based on the national surveillance data from 2006 to 2014. Among 557 cases, the median age was 33 years (range: 1–83 years), and 76% were male; 306 (55%) were classified as Japanese based on the reported name. The majority were Plasmodium falciparum infections (58%), followed by Plasmodium vivax infections (30%). Most P. falciparum cases were acquired in Africa and P. vivax in Asia/Oceania. Notification rates per 10,000 Japanese travelers for P. falciparum were highest for Africa, P. vivax were highest for Asia/Oceania, and high for both species for Papua New Guinea. Ten percent of the cases were clinically severe at the time of notification. Nearly 80% of severe cases were P. falciparum infections, and among P. falciparum cases, Japanese ethnicity was associated with severe case status ( P = 0.03). Plasmodium falciparum cases among Japanese cases showed that older age (≥ 50 years) was associated with severe case status (odds ratio = 5.4; 95% confidence interval = 1.9–15.2), adjusted for sex and healthcare access. More informative assessments are possible by accounting for the number of travelers. Older Japanese represent an important demographic to target prevention and early treatment efforts for malaria.